The causative-inchoative alternation in Turkish Sign Language and the age-of-acquisition effects on complex clauses - Kayabaşı, Demet. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2020., 2020)
This study aims to describe the causatives-inchoative alternation in Turkish Sign Language and to discuss the age-of-acquisition effects on multi-predicative constructions observed as both causative and inchoative clauses. The discussion extends itself to remarks on the structure of alternating verbs and serial verb constructions. I present and discuss the results of three tasks: a picture-description task, a picture matching task, and an acceptability judgment task. The results obtained from these tasks reveal that (i) the causative-inchoative alternation in Turkish Sign Language is attested both as labile alternation and classifier alternation, which is mostly compatible with previous accounts on this phenomenon in sign languages; however, Turkish Sign Language provides data that cannot be accounted for by Benedicto & Brentari’s (2004) account that directly links classifier handshapes and transitivity; (ii) both causative and inchoative clauses seem to have complex event structures; (iii) the structure of serial verb constructions seem to be of a mono-clausal nature; (iv) there seems to be no significant age of acquisition effects on preferring labile alternation or classifier alternation to mark the causativeinchoative alternation; yet (v) producing more complex clauses, i.e. serial verb constructions, appear to be an early acquisition group tendency.
Keywords: Sign language -- Turkey.; Sign language -- Study and teaching -- Turkey.